Moult migration of Lesser Snow Geese - Abraham, Kenneth F (Wildfowl, 1980)
Over 90% of the yearling and non-productive adult Lesser Snow Geese Anser c. caerulescens from the La Prouse Bay colony annually participate in a moult migration during mid-June, after a 4-6 week residence. Some of them undergo moult 250 km to the north, at the McConnell River, Northwest Territories. The occurrence of moult migration at other Lesser Snow Goose breeding colonies is suspected but not yet documented. Further study is required to locate moult areas of non-productive geese and to ascertain the significance of intercolony mixing.